The 18th IMT-GT International Conference on Mathematics, Statistics and Their Applications : Book of Applied Statistics (Sciendo, 2024)
The 18th ICMSA 2023 emphasized the critical role of statistical science in advancing the Sustainable Development Goals (SDGs). The conference highlighted how data science and statistical methods are essential for solving real-world problems and achieving sustainable development. The event aimed to enhance the research output of Universitas Syiah Kuala, foster a collaborative research environment, and facilitate scientific exchange with international scholars. By focusing on statistics, the conference sought to enhance the university's global reputation and contribute to government efforts to address health, environmental, and economic challenges through data-driven insights.ICMSA 2023 set a high standard for subsequent conferences, with a commitment to refining its structure and expanding its reach. The statistics-focused sessions attracted a large number of submissions, reflecting the dynamic nature of the statistics community. Following a thorough peer review process, 22 papers were selected for inclusion in the Book of Applied Statistics, ensuring that the conference's critical statistical research contributions were effectively captured and shared. Conference date, place10 - 11 April 2023, Universitas Syiah Kuala, Banda Aceh, Aceh, Indonesia Conference OrganizerICMSA 2023, Statistics Department, Universitas Syiah Kuala Editor-in-Chief Latifah Rahayu Siregar, S.Si., M.Sc, Universitas Syiah Kuala, Indonesia Managing Editor Ridha Ferdhiana, S.Si., M.Sc, Universitas Syiah Kuala, Indonesia Editorial Advisory Board Prof. Dr. Ir. Marwan, Universitas Syiah Kuala, Indonesia Prof. Dr. Ir. Agussabti, M.Si., IPU., Universitas Syiah Kuala, Indonesia Dr. Ir. Taufiq S., M.Eng., IPU, Universitas Syiah Kuala, Indonesia Prof. Dr. Taufik Fuadi Abidin, S.Si., M.Tech, Universitas Syiah Kuala, Indonesia Prof. Dr. Hizir, Universitas Syiah Kuala, Indonesia Prof. Dr. Teuku Mohamad Iqbalsyah, S.Si., M.Sc, Universitas Syiah Kuala, Indonesia Yudhie Andriyana, M.Sc., PhD, FORSTAT, Indonesia Dr. Nizamuddin, M.Info.Sc, Universitas Syiah Kuala, Indonesia Dr. Nasrullah, S.Si., M.Si., M.Sc, Universitas Syiah Kuala, Indonesia Nazaruddin, S.Si., M.Eng.Sc, Universitas Syiah Kuala, Indonesia Dr. Zurnila Marli Kesuma, S.Si., M. Si, Universitas Syiah Kuala, Indonesia Prof. Dr. Herman Mawengkang, Universitas Sumatera Utara, Indonesia Editors Dr. Selvi Mardalena, S.Stat., Universitas Syiah Kuala, Indonesia Dr. Rumaisa Kruba, S.Si, Universitas Syiah Kuala, Indonesia Dr. Rahma Zuhra, Universitas Syiah Kuala, Indonesia Dr. Muhammad Subianto, M. Si, Universitas Syiah Kuala, Indonesia Dr. Saiful Mahdi, M. Sc, Universitas Syiah Kuala, Indonesia Rini Oktavia, S.Si., M.Si., Ph.D, Universitas Syiah Kuala, Indonesia Vera Halfiani, S. Si, M. Mat, Universitas Syiah Kuala, Indonesia Language Editors Fitriana AR, Universitas Syiah Kuala, Indonesia Technical Editors Novi Reandy Sasmita, S.Si., M.Sc, Universitas Syiah Kuala, Indonesia Instructions for Authors Scientific-Committee <A href='https://sciendo-storage-bucket.s3.eu-central-1.